Analisis Filsafat dalam Tahāfut al-Falāsifah Karya Imam al-Ghazālī - Muhammad Abbas (Lembaga Yasin AlSys, 2026)
Although Imam al-Ghazālī’s Tahāfut al-Falāsifah has been widely examined in Islamic philosophical discourse, research that specifically investigates the framework of al-Ghazālī’s philosophical critique as a systematic epistemological and metaphysical analysis remains limited. This study aimed to analyze the pattern of philosophical critique developed by Imam al-Ghazālī against the metaphysical rationalism of the Peripatetic philosophers, particularly regarding causality, the eternity of the world, and God’s knowledge. The study employed a qualitative approach with a library research design, involving primary sources in the form of Tahāfut al-Falāsifah and relevant works of classical Islamic philosophy and theology, selected through purposive sampling based on textual relevance. Data were collected through document review and philosophical text analysis, and were then analyzed using a critical-philosophical approach with emphasis on epistemological, ontological, and argumentative methodological dimensions. The findings show that al-Ghazālī’s critique was not directed toward a wholesale rejection of philosophy, but rather toward delimiting rational claims when they exceed their epistemic capacity, particularly in the domain of metaphysics. These findings contribute to the development of critical Islamic philosophy theory and broaden understanding of the relationship between reason, revelation, and spiritual intuition in classical Islamic thought. The study concludes by emphasizing the importance of an integrative epistemological approach to understanding Islamic philosophy and recommends reassessing al-Ghazālī’s position as a reformer of philosophical methodology rather than merely an anti-philosophical figure, with theoretical implications for strengthening Islamic philosophy studies and practical implications for developing contemporary philosophy and Islamic studies curricula.